The specificity of emotional switching in borderline personality disorder in comparison to other clinical groups - Houben, Marlies; Bohus, Martin (Personality disorders, 2016)
In an attempt to better understand the nature of emotion dysregulation in the daily lives of persons with a borderline personality disorder (BPD), Houben et al. (2016) recently identified emotional switching, which refers to the tendency to make large changes between positive and negative emotional states over time, as a possible defining characteristic of the emotion dynamics observed in BPD. The goal of this study was to examine the specificity of these previous findings in 2 samples by comparing BPD patients (N = 43 in sample 1; N = 81 in sample 2) to patients with bulimia nervosa (N = 20), posttraumatic stress disorder (N = 28), or healthy controls (N = 28) in sample 1, and to patients with depressive disorder (N = 50) in sample 2, with respect to measures of emotional switching. Analyses of these 2 experience sampling datasets revealed that contrary to expectations, BPD patients did not differ from the clinical groups regarding their mere tendency to switch between positive and negative emotional states on consecutive moments over time and regarding the magnitude of such changes between positive and negative emotional states over time. However, all clinical groups did differ from healthy controls regarding all switch measures in dataset 1. These results indicate that emotional switching, similar to other more traditional indicators of overall changes in emotional intensity in daily life, might reflect a feature of emotional responding characterizing a range of disorders with mood disturbances.
Gesehen am 08.04.2019